Counter-hair/gemonies: hair as a site of black identity struggle in post-apartheid South Africa - Morey, Yvette Vivienne (Rhodes University, Faculty of Humanities, Department of Psychology, 2002)
This thesis aims to allow the meanings engendered by various black hairstyle choices to emerge as discursive texts with which to further explore issues of black identity in post-apartheid South Africa. It seeks to identify what, if any, new discursive spaces and possibilities are operational in the post-apartheid capitalist context, and how identities are moulded by, and in tum, influence these possibilities. Operating within a discourse analytic approach, this research did not intend to establish fixed and generalisable notions of identity, but by unpacking the discursive baggage attached to historically loaded subjectivities it is concerned with reflecting identity as an ongoing and reflexive project. Entailing a diverse selection of texts, the analysis includes self-generated texts (stemming from interviews, a focus group and participant observation), and public domain texts (stemming from online and print media articles). Chapters 5 - 9 constitute the textual analysis. Using a consumer hair care product as a text, chapter 5 serves as an introduction to discourses surrounding black hair as a variously constructed object. This focus is concerned, more specifically, with the construction of black hair as a 'natural' object in chapter 6. Chapter 7 examines black hair gemonies and the " problematic classification and de/classification of class and consumer identities. Discourses pertaining to the construction and positioning of gendered and sexual subjectivities are explored in chapter 8. Finally, chapter 9 is concerned with the operations of discourses as they function to construct essentialised or hybrid conceptions of identity. The implications for black identity construction in post-apartheid South Africa are discussed in chapter 10 alongside a deconstruction of the research method and researcher positioning.
Keywords: Hairstyles -- South Africa; Women, Black -- Race identity; Hair -- Social aspects -- South Africa; Beauty, Personal -- Social aspects -- South Africa; Hairdressing of Black people